Two Significant Factors Affecting the Dimensions of the ZnO Nanorods During Chemical Bath Deposition: Precursor Solution Concentration and HMTA Content - Koray Öztürk; Memnune Kardeş (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The effects of zinc ion concentration and hexamethylene tetramine (HMTA) content of the aqueous precursor solution on the aspect ratios of the one-dimensional (1D) ZnO nanorods during chemical bath deposition (CBD) were investigated. The ZnO nanorods were grown on these seeded substrates by the low-temperature CBD method at 95 °C for 5 h. In the first part of this investigation the zinc nitrate hexahydrate (ZNH) to HMTA molar ratio was kept constant at a ratio of 1:1 for each of the CBD solutions prepared with different Zn^(+2) ion concentrations of 0.025, 0.035, 0.050, and 0.075 M. The number densities of the nanorods (i.e., number of nanorods per unit area) were increased with the increasing concentration. In the second part, the ZNH to HMTA molar ratio was varied to differ from the 1:1 value and, in turn, to obtain the precursor solutions relatively rich in Zn^(+2) or OH^-ions. Here, the concentration of the precursor solution was kept constant at 0.05 M. The lateral growth perpendicular to the c-axis of the ZnO nanorods was found to be suppressed with the increasing HMTA content (e.g., for the ZNH to HMTA molar ratio of 0.4: 1) due to its capping effect. However, the precursor solution containing an excessive amount of HMTA led to a decrease in the probability of crystal growth, which has been attributed to the OH^- ion enrichment.